Naskah Tafsir Surat An-Nur Karya Syekh Abdul Latif Syakur (Metode Tafsir Dan Konsep Pendidikan Seks Bagi Anak) - Muhammad Jufri (PT. Pustaka Cendekia Publisher, 2024)
The Tafsir Surah An-Nûr manuscript is a work of interpretation written by hand by a Minangkabau Ulama who was born in 1882 AD, named Sheikh Abdul Latif Syakur. This research provides an understanding of how the interpretation of the letter An-Nûr written by Syekh Syakur can be an important teaching for today's life. This research uses qualitative research methods with a philological approach. The results of the discussion explain that the text of the interpretation of Surah An-Nûr contains several important main themes, namely punishment for adultery, punishment for people who accuse other people of adultery without evidence, how to deal with false accusations, motivation for marriage, house visiting etiquette, orders to cover the private parts and guard one's eyes, the concept of Divine light, encouragement to repent, the concept of sex education for children and the etiquette of mentioning the name of the Prophet. This discussion focuses more on the concept of sex education for children contained in the commentary written by Syekh Syakur, so that this can be a guide for education for children to avoid cases that are prohibited by religious norms, law and custom.